Health status of active US scuba divers 2011-2017 - Buzzacott, Peter; Edelson, Charlie; Chimiak, James (2020)
Background: Scuba diving is a physically demanding activity. Physical fitness is required to meet the routine demands of the aquatic environment, and to cope with unexpected environmental or equipment related (technical) problems. “Fitness to dive” is currently assessed by pre-training medical screening and the achievement of a minimum swimming distance. The health and physical fitness of diving trainees, however, has not been well defined. Similarly, the prevalence of diving related health and technical problems is not known. Aims: To characterise the general health and fitness of recreational scuba divers and to identify any diving related health or technical problems. Methods : Detailed health and diving questionnaires were mailed to 63 experienced divers and to 919 randomly selected subjects who had recently completed a PADI accredited diving course. Results: The overall questionnaire response rate was 55%. 72% of respondents were male and 28% female, with mean age of 27 years (range 12-66). The divers’ mean body mass index (BMI) was 23.5 (range 16-40), with 24% being overweight or obese (BMI>25). Current smokers made up 11.6% with 16.9% being ex-smokers. Most divers undertook regular exercise (88% >2 hours weekly), but only 26% swam regularly. Conditions which contraindicate diving (asthma, epilepsy or diabetes) were present in 10.4%. Minor dive related symptoms such as ear and headache were experienced by 52% of subjects. Dive-related technical problems (eg swimming difficulties, low-on-air, emergency ascent) had been experienced by 37% of respondents. Discussion: While most recently trained divers are in good health, a significant proportion are either overweight and/or do not exercise regularly. Current medical screening is not effective at excluding people considered medically unfit for diving. Despite undertaking accredited training programs, many divers had experienced avoidable technical problems when diving. Given the prevalence of these problems, the relative lack of ‘water fitness’ of most divers is of particular concern.